Frequency of Erectile Dysfunction among Smokers and Non-Smoker Men Visiting Tertiary Care Hospital Nawabshah : Frequency of Erectile Dysfunction among Smokers and Non-Smoker Men - Chandio, Sadia Ayoub; Bhalar, Zahoor Ahmed; Zardari, Inayat Ali; Ali Shar, Zulfiqar; Toor, Habib-Ur-Rehman; Ghumro, Altaf Hussain (Pakistan Journal of Health Sciences, 2025)
Epidemiological studies have shown that cigarette smoking is the independent risk factor for erectile dysfunction (ED), with smokers 1.5–2 times more likely to develop ED than nonsmokers. Additionally, long-term research has shown that quitting smoking improves erectile function, with noticeable improvements even within 24 hours of cessation. Objective: To determine the frequency of erectile dysfunction among male smokers and non-smokers at PMC Hospital Nawabshah. Methods: This research was conducted at the Department of Urology, Peoples Medical University Hospital, Nawabshah. A formal written consent /agreement was obtained from every subject/individual who fulfilled the inclusion criteria and then decided to participate. The measure divides ED into four groups based on IIEF-5 scores: mild to moderate (12–16), mild (17–21), no ED (22–25), moderate (8–11), and severe (1–7). Data were being analyzed by computer software statistical package for social sciences version 23. Frequency and percentage were computed for variables. 85.9% are confirmed to have some degree of ED, and 14.1% are found not to have ED. Results: Among the smokers, 39(27%) had mild ED, but in non-smokers, 53(37%) had mild ED. Among the smokers, 50(35%) had moderate ED, and in non-smokers, 51(36%) had moderate ED. In smokers, 64(45%) had severe ED, and in non-smokers, 38(27%) had severe ED. Conclusions: Smoking tremendously affects the erection of patients. Whereas non-smokers had a little bit less effect on erectile function.